Pengembangan "Kampung Pendekar Madiun" sebagai Pusdiklat Atlet Pencak Silat dan Wisata Raga - Indriatmiko, Pungki, Dr.Ir. Qomarun,M.M, Ir. Nurhasan, MT (2016)
Pengembangan "Kampung Pendekar Madiun" Sebagai Pusdiklat Atlet Pencak Silat dan Wisata Raga is a unity container of 11 pencak silat Organisation in Madiun City, Development of pencak silat self-defense sport, and as a first center of a Wisata Raga in Indonesia. Which later to be icon of Madiun City as a "Madiun Kota Pendekar". Located on near Stadium of Pangeran Timur Caruban City Madiun District. The facilities in sector addressed to all of people who special interested with Pencak Silat and Martial Art Sport, This development became a turning point of a cultural, physical health, spiritual. and recreational into a unified concept of development.